Solid-Gas Flow Characteristics of Drilling Bit-Rod Integral Structure - Hongtu Zhang; Ouya Zhang; Le Wei; Banghua Yao (Advances in Civil Engineering)
Sampling based on negative pressure pneumatic conveying method is an important theory in determining coal bed methane (CBM) content. The coal-gas two-phase flow path is an integrated structure composed of polycrystalline diamond compact (PDC) bit and drilling rod. In this work, CFD-DEM coupling numerical simulation was adopted to study the solid-gas flow characteristics of an integrated structure having PDC bit and gas velocity pipe under different gas velocity and solid mass flow rates. The results showed that the gas phase had a reverse velocity zone at the PDC bit. The reverse velocity zone gradually decreased with increase of gas velocity. In addition, a high-velocity band in drill pipe became apparent for the particle phase; there was an obvious bottom flow characteristic at the PDC bit and an area of the highest layer thickness in the drill pipe. Under the same gas velocity, the location of the area of the highest layer thickness shifted from the drill bit with the increase of solid mass flow rate. Increase in the gas velocity resulted in a rapid increase of the velocity of coal particles, while the bottom flow characteristics of coal particles weakened and the suspension flow gradually appeared. The results of this study are of great significance for optimizing the gas velocity based on negative pressure pneumatic conveying technique.